2017
DOI: 10.4025/actascianimsci.v40i0.36087
|View full text |Cite
|
Sign up to set email alerts
|

<b>Assessing different holding pen cooling systems through environmental variables and productivity of lactating cows

Abstract: ABSTRACT. This studyaimed to assess different holding pen climatization systems for dairy cattle through environmental variables, milk production and economic indexes. Sixteen lactating cows were used, distributed in a 4 x 4 Latin square design consisting of four groups of four animals, assessed in four periods, seven days each, and in four holding pen environments: SUN-external environment (in the sun), SHA-80%-protection polypropylenemesh shading, SHA + SPR-80% polypropylene mesh shading + water sprinkling, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 11 publications
(15 reference statements)
0
0
0
Order By: Relevance
“…allows significant reductions in these variables, promoting thermal comfort for the animals, as observed by Silva et al (2021a). Silva and Passini (2018) evaluated different cooling systems in the waiting room for crossbred cows (⅞ Holstein x ⅛ Dairy Gyr), using environmental variables, milk production, and economic indices in the summer in a tropical climate region, and observed similar results to those obtained in the present study, in which the evaporative adiabatic cooling time of 30 minutes provided the best comfort conditions for the animals.…”
Section: Morning Periodsupporting
confidence: 76%
See 1 more Smart Citation
“…allows significant reductions in these variables, promoting thermal comfort for the animals, as observed by Silva et al (2021a). Silva and Passini (2018) evaluated different cooling systems in the waiting room for crossbred cows (⅞ Holstein x ⅛ Dairy Gyr), using environmental variables, milk production, and economic indices in the summer in a tropical climate region, and observed similar results to those obtained in the present study, in which the evaporative adiabatic cooling time of 30 minutes provided the best comfort conditions for the animals.…”
Section: Morning Periodsupporting
confidence: 76%
“…High milk production cows succumb to heat stress before low production animals, due to higher nutritional requirements and metabolic heat production, which significantly alter the energy balance between the animal and the environment (Shu, Wang, Guo, & Bindelle, 2021;Burhans, Burhans, & Baumgard, 2022). Strategies that minimize this problem include managing the animal in the shade, using an evaporative adiabatic cooling system (EACS) and an automated cooling system (Silva & Passini, 2018;Tresoldi, Schütz, & Tucker, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…In a study on lactating cows in a waiting corral, Silva & Passini (2018) observed that the use of EACS, in comparison to a solely shaded environment, led to an average increase in total milk production of 1.38 kg per day. Such studies, targeting different areas of the milking parlors underscore the potential for enhancing the thermal comfort of animals waiting in handling areas.…”
Section: Resultsmentioning
confidence: 99%